Culture media for seed germination and seedling growth of Laelia autumnalis - Cabañas-Rodríguez, Marcela; Andrade-Rodríguez, María; Villegas-Torres, Oscar Gabriel; Chávez García, José Antonio; Alia-Tejacal, Iran; Juárez-López, Porfirio (Revista Mexicana de Ciencias Agrícolas, 2025)
The orchid Laelia autumnalis is endemic to Mexico and is under special protection. In vitro culture has contributed to improving the propagation of orchids from seeds. In order to micropropagate this species, an experiment was established in 2023 to evaluate eight culture media: Murashige and Skoog (MS at 100, 75, 50 and 25%), Knudson C, Dalla Rosa and Laneri, Vacint and Went, and Lindemann; all media were supplemented with 0.5 mg L-1 thiamine HCl, 100 mg L-1 myo-inositol and 3% sucrose to determine the best medium for germination of this species. Seeds were disinfected with 0.3% sodium hypochlorite (NaClO) and sown in the media in a completely randomized design with 10 replications per treatment. Germination start and percentage were recorded; seedling height, leaf length and number, root number and length, and pseudobulb diameter were evaluated at 90 days. The 25 and 50% MS media generated a higher percentage of germination (84.57 and 72.54%, respectively), which began 29 days after seeding. Growth in height (5.6 mm), leaf length (4.54 mm) and root length (5.2 mm) were higher in the MS medium at 50%, where seedlings were green. It was concluded that the best culture medium for germination and growth of L. autumnalis seedlings was the MS at 50% concentration.
Keywords: day of the dead orchid; MS medium; orchid seedlings